Social fragmentation and the decline of American democracy : the end of the social contract - Denton Fr. , Robert E. (Springer, 2020)
Contents: Acknowledgments; Contents; Chapter 1: A Divided and Selfish Nation: A United States of America No More; Notes; Chapter 2: Democracy and the "Social Contract": Prescription for Freedom and Equality; Social Contract, Liberty, and Equality; Psychological Egoism: All Interest Is Self-Interest; Political Socialization; Summary; Notes; Chapter 3: Generational Change and Social Values; The Silent Generation; Baby Boomers; Generation X; Generation Y and the Millennials; Characteristics of Today's Youth; Summary; Notes; Chapter 4: The Postmodern Culture and Political Implications; Postmodern Culture. Contents: Political Implications; Political Partisanship and Voting; Identity Politics; Rights Are Viewed as Group Based Rather than Universal; Group Interests Advocated Ahead of Universal or Common Interests; Identity Politics Encourages Social Polarization Rather than National Unity; Identity Politics Encourages "Legislative Status"; Identity Politics Encourages "Victim Politics"; Identity Politics Tends Toward "Essentialism"; Identity Politics Generates Tension between Advocated "Values" and Cultural Norms; Identity Politics Limits Freedom of Speech and Civil Discourse. Contents: Identity Politics Has Resulted in the Tyranny of the Minority; Identity Politics Is Simply "Anti-Democratic"; Social Relativism; Narcissistic Culture; Social Fragmentation and the Balkanization of America; Conclusion; Notes; Chapter 5: The Epistemological Poisoning of America; The Past as Our Prologue to Poisoning; The Good Disciple of Epistemology: The Great Debater, James Farmer Jr.; Higher Education; The Church; Journalism and Free Press; Hollywood; The Federal Government; Summary; Conclusion; Notes; Chapter 6: De-mock-racy: Comic Framing as Political Wrecking Ball. Contents: The Palinization of American Political Argument; Destroying Governor Palin; Comedy and Election 2016; Summary; Conclusion; Notes; Chapter 7: Making Black Lives Matter Today; The Great Debater: James Farmer Jr.; Farmer's History of Success; Freedom Rides: 1961; The March on Washington in 1963; The Alternative: Malcolm X; Forgetting James Farmer and His CORE Mission; Restoring Farmer and Making Black Lives Matter Again; Summary; Conclusion; Notes; Chapter 8: What Can We Do? An American Renaissance Predicated on Communicative Idealism; What Is Communicative Idealism? Contents: The Cell Phone Defeats the AK-47 in the Twenty-ƯFirst Century; Individual Freedom Defeats Collective Identity Politics; The Beloved Community Defeats the Spiral of Cynicism; Notes; Chapter 9: The Practice of Politics Today and the Greater Tomorrow; The Practice of Politics Today in America; Political Polarization; Social Fragmentation; Summary; Notes; Bibliography; Index.